2021
DOI: 10.1016/s2468-1253(21)00031-5
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of ravidasvir plus sofosbuvir in patients with chronic hepatitis C infection without cirrhosis or with compensated cirrhosis (STORM-C-1): interim analysis of a two-stage, open-label, multicentre, single arm, phase 2/3 trial

Abstract: Background In low-income and middle-income countries, affordable direct-acting antivirals are urgently needed to treat hepatitis C virus (HCV) infection. The combination of ravidasvir, a pangenotypic non-structural protein 5A (NS5A) inhibitor, and sofosbuvir has shown efficacy and safety in patients with chronic HCV genotype 4 infection. STORM-C-1 trial aimed to assess the efficacy and safety of ravidasvir plus sofosbuvir in a diverse population of adults chronically infected with HCV. Methods STORM-C-1 is a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…A previous study by Esmat et al 29 showed that a combination of SOF‐RDV in addition to ribavirin was associated with a 95.3% response rate among HCV genotype‐4 patients with or without cirrhosis. This is consistent with the STORM‐C‐1 trial, which reported that SOF‐RDV is efficient and well‐tolerated among different populations suffering from chronic HCV infection with or without comorbidities 30 . A recent molecular docking study suggested that RDV could be a potential antiviral drug against SARS‐CoV‐2 by inhibiting viral 3CLpro 31 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A previous study by Esmat et al 29 showed that a combination of SOF‐RDV in addition to ribavirin was associated with a 95.3% response rate among HCV genotype‐4 patients with or without cirrhosis. This is consistent with the STORM‐C‐1 trial, which reported that SOF‐RDV is efficient and well‐tolerated among different populations suffering from chronic HCV infection with or without comorbidities 30 . A recent molecular docking study suggested that RDV could be a potential antiviral drug against SARS‐CoV‐2 by inhibiting viral 3CLpro 31 .…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the STORM-C-1 trial, which reported that SOF-RDV is efficient and well-tolerated among different populations suffering from chronic HCV infection with or without comorbidities. 30 A recent molecular docking study suggested that RDV could be a potential antiviral drug against SARS-CoV-2 by inhibiting viral 3CLpro. 31 Nevertheless, in our study, we did not observe the superiority of a combination of SOF-RDV versus SOC.…”
Section: Discussionmentioning
confidence: 99%
“…This study was also designed to feed eligible RNA positive participants into a clinical trial entitled ‘Open label phase II/III, multicentre trial to assess the efficacy, safety, tolerance and pharmacokinetics of sofosbuvir plus ravidasvir in HCV (+/−HIV) chronically infected adults with no or compensated cirrhosis in Thailand and Malaysia’ (Malaysian Medical Research Ethics Committee, approval number NMRR-16-747-29183, coordinated by DND i , hereafter called the DND i trial). 15 16 …”
Section: Methodsmentioning
confidence: 99%
“…Following a clinical evaluation, participants were referred for enrolment into the DND i trial. 15 16 If patients were eligible and gave their written informed consent to take part in the DND i trial, they were also initiated on treatment and managed as per the DND i trial. Patients who were not eligible or who did not give consent to participate in the DND i trial were referred to the standard of care, the MOH national programme under which.…”
Section: Methodsmentioning
confidence: 99%
“…2021 was a remarkable year for medical research, highlighted by the global roll out of rapidly developed vaccines for COVID-19, the WHO recommendation of the first vaccine for malaria [ 1 ], clinical evidence of a genetic silencing method for Sickle cell disease [ 2 ], and a vastly improved new treatment for hepatitis C [ 3 ]. These and many other remarkable scientific milestones were achieved under the considerable constraints and limitations imposed by the ongoing global pandemic.…”
Section: Introductionmentioning
confidence: 99%